2012
DOI: 10.1002/jbm.b.32703
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial effect of a resin incorporating a novel polymerizable quaternary ammonium salt MAE‐DB against Streptococcus mutans

Abstract: The antibacterial properties of resins incorporating MAE-DB and the underlying mechanisms of action were evaluated. Antibacterial effects against Streptococcus mutans were tested using the film contact method, with accumulation and membrane integrity observed by scanning electron microscopy and confocal laser scanning microscopy, respectively. Quantitative PCR was used to determine expression of the S. mutans glucosyltransferase B (gtfB) gene on the surface of resins containing 10% MAE-DB. Bacterial growth was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 27 publications
2
41
0
Order By: Relevance
“…It has been shown that there is microleakage on restoration margins, and these gaps can be colonized by oral bacteria, thus resulting in secondary caries, which makes the restoration replacement necessary 22,23) . In order to prevent or diminish biofilm accumulation over composite and in the restorations margins, and also to improve the durability of prostheses, antimicrobial restorative materials have been developed, especially through the incorporation of quaternary ammonium to composite resins [24][25][26][27][28][29][30][31][32] . In 2006, a research developed by Beyth et al 24) reported that 1 wt% quaternary ammonium polyethyleneimine (QPEI) nanoparticles immobilized into composite or fluid resin had strong antimicrobial activity upon contact without leach-out of the nanoparticles and compromising in mechanical properties.…”
Section: Composite Resinmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown that there is microleakage on restoration margins, and these gaps can be colonized by oral bacteria, thus resulting in secondary caries, which makes the restoration replacement necessary 22,23) . In order to prevent or diminish biofilm accumulation over composite and in the restorations margins, and also to improve the durability of prostheses, antimicrobial restorative materials have been developed, especially through the incorporation of quaternary ammonium to composite resins [24][25][26][27][28][29][30][31][32] . In 2006, a research developed by Beyth et al 24) reported that 1 wt% quaternary ammonium polyethyleneimine (QPEI) nanoparticles immobilized into composite or fluid resin had strong antimicrobial activity upon contact without leach-out of the nanoparticles and compromising in mechanical properties.…”
Section: Composite Resinmentioning
confidence: 99%
“…The results had shown that modified resins greatly decreased biofilm metabolic activity, colony-forming unit (CFU), and lactic acid with strong and durable antimicrobial properties and remineralization, while matching the load-bearing capability of commercial composites without antimicrobial properties. In similar studies, Huang et al 28,29) developed resins containing 10 wt% of polymerizable QACs, 2-methacryloxylethyl dodecyl methyl ammonium bromide (MAE-DB) or 2-methacryloxylethyl hexadecyl methyl ammonium bromide (MAE-HB). And they compared these new compounds with unmodified resins.…”
Section: Composite Resinmentioning
confidence: 99%
See 1 more Smart Citation
“…1). Recently, with the attempts to increase the amount of antibacterial quaternary ammonium monomers that can be incorporated in adhesives and subsequently enhance the antibacterial activity of the modified material without compromising biocompatibility, new antibacterial monomers with two polymerizable methacrylic moieties have been developed [14,25,26].…”
Section: Non-agent-releasing Antibacterial Adhesivesmentioning
confidence: 99%
“…Metal ions, such as Ag 1 and Cu 21 , are widely used as antibacterial agents for silk fabrics, and the influence of pH value of metal solution on the absorption of fabric surface is also investigated. 10 The in-situ synthesis approach assisted by UV light was developed to deposit silver nanoparticles onto the surface of silk fabrics with antibacterial activity, which could also postpone thermal degradation of silk fabrics.…”
Section: Introductionmentioning
confidence: 99%